2008
DOI: 10.1073/pnas.0808249105
|View full text |Cite
|
Sign up to set email alerts
|

Dephosphorylation by calcineurin regulates translocation of Drp1 to mitochondria

Abstract: Changes in mitochondrial morphology that occur during cell cycle, differentiation, and death are tightly regulated by the balance between fusion and fission processes. Excessive fragmentation can be caused by inhibition of the fusion machinery and is a common consequence of dysfunction of the organelle. Here, we show a role for calcineurin-dependent translocation of the profission dynamin related protein 1 (Drp1) to mitochondria in dysfunction-induced fragmentation. When mitochondrial depolarization is associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

31
890
3
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 955 publications
(927 citation statements)
references
References 36 publications
(41 reference statements)
31
890
3
3
Order By: Relevance
“…4E), which is consistent with prior reports of Pim-1 binding to and stabilizing proteins (19), raising the possibility that Pim-1 promotes Drp1 cytosolic sequestration by association. Drp1 mitochondrial shuttling is inhibited by phosphorylation at S 637 , with Drp1-S637 dephosphorylation modulated by calcineurin (21,28). Dephosphorylation of Drp1-S637 prevents cytosolic sequestration of Drp1 and promotes mitochondrial fission, which is consistent with our observation of increased levels of phospho-Drp1 in Pim-1 overexpressing transgenic hearts.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…4E), which is consistent with prior reports of Pim-1 binding to and stabilizing proteins (19), raising the possibility that Pim-1 promotes Drp1 cytosolic sequestration by association. Drp1 mitochondrial shuttling is inhibited by phosphorylation at S 637 , with Drp1-S637 dephosphorylation modulated by calcineurin (21,28). Dephosphorylation of Drp1-S637 prevents cytosolic sequestration of Drp1 and promotes mitochondrial fission, which is consistent with our observation of increased levels of phospho-Drp1 in Pim-1 overexpressing transgenic hearts.…”
Section: Discussionsupporting
confidence: 80%
“…Recombinant Drp1 was used as substrate, and γ-32 p-ATP incorporation was measured with recombinant active Pim-1 and recombinant kinase dead Pim-1. Mutation of serine 637 of Drp-1 to an alanine residue that cannot be phosphorylated (S637A) induces mitochondrial translocation of Drp-1 and fragmentation, whereas mutation to phosphomimetic aspartic acid (S637D) inhibits translocation (21). The relevance of the serine 637 residue for Pim-1 mediated effects on Drp-1 subcellular localization and mitochondrial phenotype was assessed by coexpression of Drp1-S637A with either Pim-1-mCherry or mCherry alone as a control.…”
Section: Drp1mentioning
confidence: 99%
“…However, it remains possible that VacA-induced ΔΨ m dissipation induces Drp1-dependent fission. Support for this idea comes from unrelated studies that demonstrated that mitochondrial depolarization in HeLa cells induced a sustained cytosolic calcium rise, followed by calcineurin-mediated dephosphorylation of Drp1 at Ser637 as a mechanism to drive Drp1 translocation to mitochondria (56). VacA is sufficient to induce ΔΨ m dissipation (19) and increases in cytosolic calcium (57), but a potential link between elevated cellular calcium or calcineurin action and Drp1-dependent mitochondrial fission within VacA-intoxicated cells remains to be evaluated.…”
Section: Discussionmentioning
confidence: 91%
“…Drp1 appears to be responsible for this fragmented phenotype as studies have demonstrated that ablation of Drp1 reduces mitochondrial fragmentation during apoptosis (Estaquier et al, 2007;Frank et al, 2001;Karbowski et al, 2002;Sugioka et al, 2004), while overexpression of dominant negative Drp1 also prevents apoptosis-induced mitochondrial fragmentation (Arnoult et al, 2005b;Frank et al, 2001 Cribbs et al, 2007). However, following a death stimulus such as staurosporine, the phosphatase calcineurin dephosphorylates Drp-1, triggering its translocation from the cytosol to mitochondria, thus increasing fission (Cereghetti et al, 2008;Cribbs et al, 2007). In addition, overexpression of the BH3-only protein Bik induces Drp1-dependent mitochondrial fission by a pathway dependent on calcium signalling (Germain et al, 2005).…”
Section: Accepted M Manuscriptmentioning
confidence: 99%